Kesesuaian Praktik Bagi Hasil Pertanian di Kampung Babakan Nagrak dengan Prinsip-Prinsip Hukum Islam - Sobandi, Nia; Pusvisasari, Lina; Nurazizah, Rayi (Tasyri' : Jurnal Muamalah dan Ekonomi Syariah, 2026)
This study examines the conformity of agricultural profit-sharing practices in Babakan Nagrak Village with Islamic legal principles. Previous studies on muzāra‘ah have mostly focused on normative aspects, while empirical practices at the village level remain underexamined. This research aims to fill that gap by analyzing the actual cooperation between landowners and tenant farmers. This study employs a qualitative approach using a case study method through field observation, in-depth interviews with three key informants, and documentation. The findings show that profit-sharing is implemented using a 1/2–1/2 and 1/3–2/3 ratio based on capital and labor contributions. Generally, the practice fulfills the main elements of a muzāra‘ah contract, such as mutual consent (tarāḍī) and agreed profit ratios. However, the absence of written agreements and unclear risk allocation in case of crop failure potentially leads to elements of gharar. This study contributes by proposing a simple administrative model for muzāra‘ah contracts to improve transparency and fairness based on fiqh muamalah principles. Practically, it can serve as a reference for rural communities in strengthening Sharia-compliant agricultural cooperation.